Stomatal Frequency and Distribution in Mustard (Brassica juncea L.) in Relation to Soil Moisture - Paul, NK; Mondal, RK (Bangladesh Journal of Scientific and Industrial Research, 2008)
Effect of soil moisture on stomatal frequency and distribution of mustard was studied. The irrigated plants had significantly higher number of stomata on both the adaxial and abaxial surfaces of leaf than the rainfed plants. No significant effect of soil moisture on stomatal frequency of stem and pod was found. Key words: Mustard, soil moisture, stomatal frequency, pod. Bangladesh J. Sci. Ind. Res. 42(3), 353-356 2007